Influence of legal status on the uptake of cannabis in young people. Issue 4 (July 2016) - Dirisu, Osasuyi; Shickle, Darren; Elsey, Helen
Abstract : Purpose of review: Policies that limit young people's access to cannabis may reduce early onset of use and minimize health-related harm. This review article provides an update of recent research examining the influence of the cannabis policy frameworks on the use of cannabis by young people. Recent findings: There are significant concerns that ongoing policy changes in favour of legalization will increase the uptake of cannabis by young people. Evidence to support a causal effect of cannabis policy changes on increased uptake by young people is lacking; more time may be needed to assess the impact because the policies are still evolving. Policy changes in favour of legalization were associated with reduced risk perception although this may be a cause or consequence. The need to situate the impact of these policies in the context of specific policy features, social norms and perceptions about cannabis has been highlighted. Summary: A more nuanced understanding of the impact of the legal status of cannabis on young people is needed to build evidence for future policy options. The impact of these policies may not be immediately apparent but limiting young people's access to cannabis must be prioritized during policy deliberations.